Winning on Social Media: Candidate Social-Mediated Communication and Voting During the 2016 US Presidential Election. (March 2019) - Macafee, Timothy; McLaughlin, Bryan; Rodriguez, Nathian Shae
The 2016 US Presidential Election provided an opportunity to examine how political candidates' use of social media can affect voting intentions. This study considers how political candidates can use social media to increase potential supporters' perceptions that they will win the election, providing them extra motivation to go out and vote. Results from a two-wave survey provide evidence that following the in-group candidate (Trump or Clinton) relates to voting intentions through the increased belief that the candidate would win. However, this mediation effect occurs for only supporters of Trump or Clinton, but not for partisans of the opposing party.